2013
DOI: 10.1016/j.soscij.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Young maternal age and low birth weight risk: An exploration of racial/ethnic disparities in the birth outcomes of mothers in the United States

Abstract: This study considers how low birth weight (LBW) prevalence varies by race/ethnicity and maternal age and explores mechanisms that explain disparities. Results show that maternal age patterns in LBW risk for African Americans differ from whites and foreign- and U.S.-born Hispanics. Background socioeconomic disadvantage, together with current socioeconomic status and smoking during pregnancy, explain almost all of the LBW disparity between white teenage mothers and their older counterparts. These findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
3
35
1
3
Order By: Relevance
“…Although the incidence of LBW was higher in mothers of lower age group (17–19 years) in both TGW and HW, the difference was found to be non‐significant. This finding was consistent with some of the previous research . Fraser et al .…”
Section: Discussionsupporting
confidence: 94%
“…Although the incidence of LBW was higher in mothers of lower age group (17–19 years) in both TGW and HW, the difference was found to be non‐significant. This finding was consistent with some of the previous research . Fraser et al .…”
Section: Discussionsupporting
confidence: 94%
“…The associations between cardiovascular disease and diabetes PRS and the lipids are as expected from the epidemiological literature [36,37], while the suggestive evidence for associations between anorexia and neuroticism PRS and insulin support the proposed role for genetics in the shared aetiology between insulin and cognitive function [40]. It has been suggested that social disadvantage underlies the low maternal age-low birth weight link [44]; nevertheless, our data suggest that whatever the underlying causal factor is, it is under a degree of genetic control.…”
Section: Prs Were Calculated For 5404 Participants With Genotype Datasupporting
confidence: 67%
“…[5][6][7][8] Additional hypotheses, including normative differences in childbearing patterns by age, 9 allostatic load, 6,10-12 the developmental origins of health and disease, 13 and the life-course framework, 11,[14][15][16] have been developed to advance our understanding of disparities in birth outcomes. [16][17][18][19][20][21][22][23][24] The extent to which the various hypotheses apply to all minority women at all points in their reproductive lives is not clear. For weathering specifically, researchers often use white women in their twenties as the universal reference group, an approach that does not sufficiently account for the increased baseline risk of poor outcomes among black women at all ages, nor for the increasing risk of poor birth outcomes with advancing maternal age for all women.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Additional hypotheses, including normative differences in childbearing patterns by age, allostatic load, the developmental origins of health and disease, and the life‐course framework, have been developed to advance our understanding of disparities in birth outcomes . The extent to which the various hypotheses apply to all minority women at all points in their reproductive lives is not clear.…”
Section: Introductionmentioning
confidence: 99%